(3MGTjI bhd GMeO Ydi GdahGFO GdafGQjI Ydi EjSGZhLjs - (3GdYeQj GdMfaj, CHh GdYHGS, GHf GdNVQ, bhd CMeO (B- (3TgGH GdOjf, CMeO Hf eMeO Hf YeQ Hf eSde, (B785 (3g`s
(3ChdgG (B:s
(3MeOG dc Ydi eG efMJ Hg ef eYGQa GdCaGVd adeG cGfJ GdahGFO GdafGQjI Ydi eG dG Yf GdZehV hGdEZdGb heY gPG ENhGf GdReGf QGZHhf ajgG ZGjI QZHI hGTJjGb YdbJ YdjgG eG jcTa GdZdGb hjRj GdZehV MJi jJjSQ dges
(3BNQgG (B:s
(3bhdg hGdYeOI gh GdHQgGf bjd aj bhdg JYGdi GOY Edi SHjd QHc HGdMceI hGdehYXI GdMSfI hLGOdge HGdJj gj CMSf Cf GdMceI CTGQ Edi GdHQgGf hGdehYXI Edi GdNWGHI hGdLO Edi GdLOd JeJs
(3GdJCQjN ef QSGdI EjSGZhLj GdeDQNI aj GdeLehY HNW bQjH Ch eWGHbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/225s
(3GdCYdGe (B1/225s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdadSaI hGdefWbs